PENGARUH CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN ,KINERJA PERUSAHAAN TERHADAP FINANCIAL DISTRESS (PERUSAHAAN PROPERTIES &REALESTATE DIBURSA EFEK INDONESIA 2020-2024) - Soemaryono Soemaryono; Ferlyana Agustin (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the impact of corporate governance, ownership structure, and company performance on the financial distress conditions of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Financial distress refers to a decline in a company's financial health that can lead to bankruptcy if not promptly addressed. Effective corporate governance implementation, an efficient ownership structure, and optimal company performance are expected to reduce the likelihood of financial distress. This study employs a quantitative approach using secondary data obtained from the annual financial reports of property and real estate companies listed on the IDX between 2020 and 2024. A purposive sampling method was used based on predetermined criteria. Data analysis was conducted using logistic regression to examine the influence of the independent variables on financial distress. The research findings reveal that corporate governance, ownership structure, and company performance collectively influence financial distress. Individually, corporate governance and company performance have a significant impact on financial distress, whereas ownership structure shows varying effects depending on the specific characteristics of each company. These results indicate that improving the quality of corporate governance and achieving strong financial performance can be key factors in mitigating financial distress.